Peran Guru PAI dalam Menanamkan Pendidikan Multikultural dan Moderasi Beragama pada Siswa Kelas VII SMP Negeri 2 Galang - Muhammad Ghozali Ma'arif (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study is motivated by the importance of education in instilling values of tolerance and religious moderation amid students' cultural and religious diversity. The purpose of this research is to describe the role of Islamic Religious Education (PAI) teachers in fostering multicultural education and religious moderation among seventh-grade students at SMP Negeri 2 Galang. This research employed a descriptive qualitative method with data collected through interviews, observation, and documentation. The findings reveal that PAI teachers act as educators, spiritual guides, and moral role models in shaping students' moderate character through the integration of multicultural values in learning, the habituation of tolerant attitudes, and inclusive religious activities. However, challenges remain, including limited instructional time, students' lack of understanding, social media influence, and insufficient systemic support from the school. The implications of this study highlight that PAI teachers play a crucial role in realizing character education based on moderation and multicultural awareness to create a peaceful and harmonious school environment.